Considerations for the design and execution of protocols for animal research and treatment to improve reproducibility and standardization: "DEPART well-prepared and ARRIVE safely". Issue 3 (March 2017) - Smith, M.M.; Clarke, E.C.; Little, C.B.
Summary: Objective: To review the factors in experimental design that contribute to poor translation of pre-clinical research to therapies for patients with osteoarthritis (OA) and how this might be improved. Methods: Narrative review of the literature, and evaluation of the different stages of design conduct and analysis of studies using animal models of OA to define specific issues that might reduce quality of evidence and how this can be minimised. Results: Preventing bias and improving experimental rigour and reporting are important modifiable factors to improve translation from pre-clinical animal models to successful clinical trials of therapeutic agents. Despite publication and adoption by many journals of guidelines such as Animals in Research: Reporting  In Vivo  Experiments (ARRIVE), experimental animal studies published in leading rheumatology journals are still deficient in their reporting. In part, this may be caused by researchers first consulting these guidelines  after  the completion of experiments, at the time of publication. This review discusses factors that can (1) bias the outcome of experimental studies using animal models of osteoarthritis or (2) alter the quality of evidence for translation. We propose a checklist to consult  prior  to starting experiments; in the Design and Execution of Protocols for Animal Research and Treatment (DEPART). Conclusions: Following DEPART during the design phase will enable completion of the ARRIVE checklist at the time of publication, and thus improve the quality of evidence for inclusion of experimental animal research in meta-analyses and systematic reviews: "DEPART well-prepared and ARRIVE safely".